A descriptive study Professional and socio-cultural profiles of mental health workers in Turkey - Sitrava-Günenç, Sevilay (İstanbul Bilgi Üniversitesi, 2010)
[Abstract Not Available]
Betimleyici çalışma Türkiye'deki ruh sağlığı çalışanlarının profesyonel ve sosyo-kültürel profilleri